Gambaran Faktor Risiko Penurunan Daya Penglihatan pada Pekerja Bengkel Las di Kecamatan Oebobo - Skolastika Marista Nadu; Johny A. R. Salmun; Agus Setyobudi (Universitas Nusa Cendana, 2022)
Welders are one of the professions that have a high risk of visual complaints and eye injuries rank second in workers thay may lead to a decrease in visual acuity. This research is a descriptive study which aims to describe the risk factors for decreasing vision in welders in Oebobo District, Kupang City in 2020 with a total sample of 32 people. The results showed that a half of workers were ≥ 30 years (50%), worked with a period of < 3 years (56.25%), had long exposure > 8 hours/day (56.25%), used welding glasses (68.75%), and had complaints of decreased vision (68.75%). Welding business owners need to provide welding glasses (goggles) to be used in welding activities. Education related to occupational health and safety in the welding sector is recommended to increase prevention-related knowledge for eye problems for both welders and business owners.